A Trio of Perspectives on Corruption : Bias, Speed Money and “Grand Theft Infrastructure” - Kenny, Charles; Klein, Michael; Sztajerowska, Monika (2012)
A number of recent survey articles express hope that new data from enterprise surveys would shed new light on corruption complementing the corruption perception index by Transparency International. The paper explores this using the World Bank's Enterprise Survey data globally and not just the data on Eastern Europe and Central Asia that have been used before. The authors find that in general the Enterprise Survey data provide aggregate views on corruption that are similar to the corruption perception index. However, massive differences exist for key countries, such as China and India. This suggests that idiosyncratic, country-specific biases are at work in one or both data sources. The authors use the Enterprise Survey data and relate them to measures of bureaucratic complexity from the World Bank's Doing Business data, finding that more red tape is associated with higher corruption. The data are also consistent with the view that bribe payments reduce the burden of red tape. Finally, the paper looks at corruption in infrastructure. It has been suggested that the natural monopoly characteristics of infrastructure provide the lever to extract bribes. However, based on data on price-cost gaps, the authors find that infrastructure ventures in power and water typically charge prices below cost in developing economies, not anywhere near monopoly prices. Furthermore, the Enterprise Surveys do not suggest that infrastructure-related bribe payments are more significant than those, for example, related to tax payments or various forms of licensing. Existing sources on bribery surrounding specific projects suggest that the value of bribe payments may not be the biggest problem but the choice of uneconomic and inefficient projects. If infrastructure ventures were entirely dependent on revenue from user fees, they could not afford to pursue inefficient projects, thus reducing the cost of corrupt activity to society. Monopoly pricing would be better than the typical current pricing policy.